Redefining low Earth orbit as a parking orbit for flexible and economical Earth departure in deep space missions - Takei, Yuto; Saiki, Takanao; Tsuda, Yuichi (Frontiers in Space Technologies, 2022)
Numbers of deep space probes are currently in operation with diverse destinations and objectives. For example, the Japanese Hayabusa2 and the U.S. OSIRIS-REx missions are both sample returns, targeting different near-Earth asteroids. Europe’s ExoMars and the U.S. Perseverance are orbiting and roving Mars as precursors of future manned explorations. Conventionally, deep space missions require dedicated launch vehicles for each mission. The interplanetary Earth departure trajectory from the low Earth orbit (LEO) usually lacks flexibility and efficiency. Furthermore, innovative and reusable launch systems have been researched and developed by multiple organizations including the private sector such as SpaceX and Blue Origin. It is expected that the unit cost per launch weight to LEO be significantly reduced by rideshare mass transportation executed by reusable mega launchers in the near future. This study aims to fill the transportation gap between LEO and deep space by realizing the flexible and economical interplanetary Earth departure without sacrificing the arbitrariness of LEO, target V-infinity vector, and target Earth departure epoch. Thus, the one-revolution Earth free-return orbit (1rEFRO) and the consequent Earth gravity assist (EGA) are introduced to separate the velocity increment and direction adjustment. The planetary free-return and EGAs are common in interplanetary missions; however, a comprehensive study on the flexibility, economic efficiency, and arbitrariness of the sequence (1rEFRO+EGA) originating from LEO was not explicitly found. After describing the necessary coordinate frames, LEO’s orbital elements, 1rEFRO, and the terms flexibility and economic efficiency are defined in Section 2. Then in Section 3, the two-body-based preliminary orbit design method is proposed and formulated. Section 4 aims to reveal LEO’s comprehensiveness as efficient parking orbits when adopting the 1rEFRO+EGA sequence, using the newly proposed “〖ΣV〗_Et LEO i-Ω Diagram”. Section 5 describes a detailed orbit design constructed based on multi-body propagation and optimization to confirm the feasibility, flexibility, and economics of the solution and the usefulness of the initial solution given by the preliminary design method formulated in Section 3.